Renal function during profound hypothermia in the dog - Isaacson, Leon Charles (Department of Medicine, 2020)
During the academic year 1960-1961, the Department of Experimental Surgery, of the University of Cape Town, engaged in a series of experiments concerning the production of profound hypothermia in dogs. Hypothermia was induced by blood-stream cooling, via a heat exchanger incorporated in an extra-corporeal pump-oxygenator system (ef Appendix A). Progress was such that by midyear postoperative survival of experimental animals was assured. At this juncture, it was suggested that, as a member of the Renal-Metabolic Group of the Department of Medicine, I co-operate wit the surgeons, in a study of renal function during profound hypothermia in the dog. This thesis details our progress and results.